Islamic brotherhood's influences on early Medina society - Abu Hassan, Muhammad Ikram; Bahanizam, Nurshafiqah Tunnur; Misrijan, Nor Masturah; Yusni, Seri Nur Athirah; Hazman, Nurhanani (Almakrifah Resources, 2025)
Brotherhood is an important part in building the Islamic society. The main question of this research is how strong and harmonious the link of Islamic brotherhood can make a social structure among people from diverse origins. This research looks at how Islamic brotherhood affected the growth of the Medina community in the early days of Islam. The Medina community was made up of people from many different ethnic and tribal origins, yet Prophet Muhammad PBUH was able to bring them all together in only a short period of time. The objective of this article is to look at how the Islamic Brotherhood helped bring early Muslims in Medina together and to look at the manner in which this brotherhood affected the Medina community's growth in terms of its social, economic, and political aspects. This research uses qualitative methods to look at texts from Sirah Nabawiyya books, academic publications, and scholarly essays. The study's findings showed that the brotherhood that the Prophet PBUH started had a big impact on the Medina community's social, economic, and spiritual life. This link not only closed the gap between the two major factions (the Muhajirin and the Ansar), but it also helped Muslims stay politically united, socially stable, and economically strong at the period. In conclusion, Islamic brotherhood is an essential part of developing an Islamic community and has been a useful model for community development across time. This research gives us a better idea of the social, economic, and political ways to make the Islamic society stronger.